2018
DOI: 10.1155/2018/7503421
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Telemonitoring for Patients on Warfarin after Discharge from Hospital

Abstract: Objective To evaluate the impact of telephone follow-up service on clinical outcomes in patients on warfarin when discharged from hospital. Methods This randomized controlled trial was conducted at a general hospital in Thailand. Patients aged ≥20 years who were prescribed warfarin when discharged were eligible to participate in this study. They were randomly allocated, using a computer generated random number, to receive either telephone follow-up intervention or usual care. Participants in the intervention g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…After removing duplicate studies, 2 authors independently reviewed and excluded another 5652 studies that did not meet predetermined selection criteria, based on the title and abstract of each paper. After reading 33 eligible full-text studies, 18 were excluded and 15 were selected for inclusion in the analysis [ 12 , 19 - 31 ]. The systematic search results are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicate studies, 2 authors independently reviewed and excluded another 5652 studies that did not meet predetermined selection criteria, based on the title and abstract of each paper. After reading 33 eligible full-text studies, 18 were excluded and 15 were selected for inclusion in the analysis [ 12 , 19 - 31 ]. The systematic search results are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…There were 11 studies that met our inclusion criteria with a total of 7732 participants of which five were reported across multiple papers (Figure 1). 14–35 The participants included 3372 females and 4360 males with a weighted mean (SD) age of 60.9 (4.2) years; follow up ranged from 3 to 54 months. Just over half the studies were set in the United States of America, with studies set in one each of the United Kingdom, Thailand, Jordan and Iran (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…25 Only one study reported clinically significant adverse events. 33 It reported an equivalent number of participants in both groups who experienced bleeding events and thrombotic events (e.g. cerebrovascular events, pulmonary embolism or myocardial infarction).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations